Caregiving Load and Respite Service Use: A Comparison between Older Caregivers and Younger Caregivers. Issue 1 (2nd January 2018) - Shi, Junrong; Chan, Keith; Ferretti, Lisa; McCallion, Phillip
ABSTRACT: Study aims were to explore differences in predictors of respite care use between older (aged 65+) and younger caregivers (aged 18–64 years), and associations between caregiving load and respite care use using multivariate logistic regression analysis and unpaid caregiver ( n = 10, 500) data from the 2009 California Health Interview Survey. Caregiving load comprised number of care recipients, weekly hours in caregiving, and caregiving duration. Variables with a significant association with respite care for older caregivers were female gender, income, and health insurance. For younger caregivers, respite care use associations were with ethnicity, caregiving relationship, education, and availability of substitute help.